The NASA/JPL program in microgravity fundamental physics - Israelsson, U.E.; Lee, M.C. (Физика низких температур, 1998)
The National Aeronautics and Space Administration (NASA) has been supporting research in
microgravity low temperature physics tor about 20 years. In the last 10 years the program has seen
srgnrhcant growth rn the number ot funded investigations and in the breadth of the research activities
being pursued. Currently, flight experiments are being performed exclusively on the Space Shuttle. For
the future, a cryogenic Space Station facility is being developed by the Jet Propulsion Laboratory and
industrial partners to support the microgravity needs ot the international scientific community. The
facility will be attached to the Japanese Experiments Module’s Exposed Facility and will operate with
a 6 month helium cryogen lifetime. Flights of the facility are planned at 2 year intervals starting in 2003
with each flight accommodating multiple scientific experiments. Capabilities, conceptual designs and
development plans for the facility are discussed along with a summary of potential near term flight
candidate experiments.